INFLUENCE OF PARAMETERS OF THE TRAFFIC- LIGHT REGULATION CYCLE ON THE ROAD CAPACITY OF REGULATED INTERSECTIONS - K. Isakov; L. N. Stasenko; A. Sh. Altybaev; D. Daiyrbekova (Вестник СибАДИ, 2019)
Introduction. Road capacity refers to the main indicators, characterizing the working conditions of streets and highways. For the street capacity as a whole the minimum value of a certain section is taken, which includes adjustable intersections in one level.The capacity of intersections in one level largely determines the performance of the entire city transport system, the level of comfort and safety of movement. Therefore, the increase of the regulated intersections’ capacity is necessary not only for improving the traffic conditions, but also for improving the economy and movement comfort of the entire stream of cars on the street.Materials and methods. Traffic jams form almost on all regulated intersections of the city and stretch more than ten meters. Traffic jams becomes commonplace not only during rush hours, but also during the whole day.Results. The paper presents the results of the dynamic research of the adjustable intersections’ throughput observed while changing the parameters of the traffic lights’ cycle.Discussion and conclusions. The authors monitor the traffic flow conditions on the regulated intersections of Bishkek to study the degree of influence of the traffic light regulation cycle parameters on the road capacity of the regulated intersections in one level. The authors select 6 problem intersections as research objects.